Nutrition education : linking research, theory, and practice - Contento, Isobel R.; Koch, Pamela A. (Burlington, MA : Jones & Bartlett Learning, 2026)
"Nutrition Education: Linking Research, Theory, and Practice provides a straightforward, user-friendly model for designing effective nutrition education programs that address the personal and environmental factors affecting individuals' food choices and assists them in adopting healthy behaviors throughout their lifetime. Built around the six-step DESIGN process, the text integrates research, theory, and practice and provides advice and direction on designing, implementing, and evaluating theory-based nutrition education"--
Nutrition Education for Today's Complex World -- An Overview of Nutrition Education : Motivation, Ability, and Support for Behavior Change -- Nutrition Education DESIGN Procedure and Step 1: Decide Behavior -- Step 2: Exploring Motivating Determinants for Behavior Change -- Step 2: Exploring Facilitating Determinants of Behavior Change -- Step 3: Selecting Theory for Behavior Change -- Step 4: Indicating Educational Objectives for Behavior Change -- Step 5: Generating Educational Plans -- Enhancing Motivation for Behavior Change -- Step 5: Generating Plans -- Facilitating Ability for Behavior Change -- Nail Down the Evaluation Plan: Step 6 -- Creating Environmental Supports for Behavior Change -- Delivering Nutrition Education in Group Settings -- Media Supports and Other Channels for Nutrition Education -- Working with Diverse Age and Cultural Groups -- Nutrition Educators as Change Agents.
Includes bibliographical references and index.
In English
NBL010825
Keywords: Dietetics -- education; Health Education -- methods; Feeding Behavior; Health Behavior